Integrated use of otolith shape and microchemistry to assess Genidens barbus fish stock structure. (31st October 2021) - Rodrigues Maciel, Thaís; Vianna, Marcelo; Maichak de Carvalho, Barbara; Miller, Nathan; Avigliano, Esteban
Abstract: Otolith composition (edge vs core: Mg/Ca, Mn/Ca, Zn/Ca, Sr/Ca, Ba/Ca) by LA-ICP-MS and Elliptic Fourier analysis were integrated to evaluate spatial segregation of adult and juvenile stages of Genidens barbus from specimens collected from five coastal areas off Brazil (Paraíba do Sul River, Guanabara Bay, Itapanhaú River mouth, Paranaguá Bay), Argentina and Uruguay (La Plata Estuary). Fisheries of this diadromous catfish have largely collapsed in the southwest Atlantic coastal region due to overexploitation. An understanding of population structure is now critically needed for improved management strategies for this endangered species. PERMANOVA based on otolith edge chemistry showed significant differences ( p < 0.05 ) between all sites, except Itapanhaú River and Paranaguá Bay. Shape, by comparison, found significant differences between all sampling sites, except Guanabara Bay and Paranaguá Bay, and Itapanhaú River and Paranaguá Bay. Discriminant analysis cross-classification success based on chemistry ranged from 33.3 (Paranaguá Bay) to 100% (La Plata Estuary), and 66.7 (Paranaguá Bay) to 100% (La Plata Estuary) for otolith edges (mean = 61.3%) and cores (mean = 78.9%), respectively. For otolith shape, the jackknifed rate (mean = 45.9%) was relatively low for all sites (32.1–44.7%) except La Plata Estuary (67.6%). Although we do not find otolith shape to be particularly useful; otolith microchemistry supports the presence of different management units. The results revealed that on a small geographic scale ( 300 km) microchemistry might not be efficient to discriminate between some sampling sites. Highlights: Spatial segregation in young and adult stages of Genidens barbus was studied. Otolith microchemistry and shape are potential tools for stock identification. Results suggest the presence of different management units. High percentages of classification suggest low connectivity between some populations. The populations should be managed as separate groups.